2019
DOI: 10.1002/tesj.461
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ reflective practice, job satisfaction, and school context variables: Exploring possible relationships

Abstract: Concentrating on job satisfaction and five school context variables—teacher autonomy, collegial support, time pressure, student demotivation, and student discipline problems—this study explored the interplay of these variables with reflective teaching and their relative contributions to prediction of teacher reflection. Data were collected from 181 Iranian high school teachers. The results of correlational analysis revealed that all independent variables significantly correlated with teacher reflection. Strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To implement CSA, empowering learners with higher-order thinking skills is strongly suggested (Amirian et al, 2022;Heydarnejad, Abdel-Al Ibrahim, et al, 2022). RT is a problem-solving tool and enables learners to stop, step back, think deeply, measure, analyze, synthesize, and make thoughtful decisions (Aliakbari et al, 2020;Namaziandost, Heydarnejad, & Rezai, 2022). As a zoom lens strategy for taking a deeper look at assessment, RT calls learners' attention, and they gain an appreciation for the cognitive and affective window of language learning and assessment (Ayoobiyan & Rashidi, 2021;Shirazizadeh et al, 2019;Syairofi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To implement CSA, empowering learners with higher-order thinking skills is strongly suggested (Amirian et al, 2022;Heydarnejad, Abdel-Al Ibrahim, et al, 2022). RT is a problem-solving tool and enables learners to stop, step back, think deeply, measure, analyze, synthesize, and make thoughtful decisions (Aliakbari et al, 2020;Namaziandost, Heydarnejad, & Rezai, 2022). As a zoom lens strategy for taking a deeper look at assessment, RT calls learners' attention, and they gain an appreciation for the cognitive and affective window of language learning and assessment (Ayoobiyan & Rashidi, 2021;Shirazizadeh et al, 2019;Syairofi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By extension, one might think that a heated research trend—as, for example indicated by the large number of “research publications that refer to the term ‘translanguaging’” (Li & Garcia 2022, p. 2)—might not be necessarily interpreted as a significant indicator of actual language teaching and learning practices. Given teachers' working conditions and the sources of their teaching ideas and practices in Iran and elsewhere (e.g., Aliakbari, Khany, & Adibpour, 2020; Crookes & Arakaki, 1999; Johnston, 1997), even if they do hear about critical ideas, they may not apply them because of the overwhelming influence of the images and forces of mainstream language teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been found to have a favorable influence on job satisfaction [ 31 ]. According to the findings of the study, workers who received high levels of social support reported higher levels of happiness in their jobs compared to workers who received low levels of social support.…”
Section: Literature Reviewmentioning
confidence: 99%